1988
DOI: 10.1111/j.1365-2842.1988.tb00169.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro temperature rises during visible‐light curing of a lining material and a posterior composite

Abstract: The aim of this study was to measure the rise in temperature during: (i) a single cycle of a curing light unit, (ii) the polymerization of a layer of light-cured lining material, and (iii) the polymerization of a light-cured posterior composite material, and also during combinations of these individual procedures. Experimental work was undertaken in vitro and measurements were made using a thermocouple placed centrally in an insulated PTFE well. Large temperature rises occurred with the use of the curing light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 8 publications
1
20
0
2
Order By: Relevance
“…6,7 Most of the current adhesive systems use an acidic conditioner to prepare the dentin surface for the bonding components. 8 When dentin is etched with phosphoric acid concentrations, the smear layer is completely removed and the dentin surface is morphologically changed due to the dissolution of hydroxyapatite crystals. This process widens the dentinal tubules and exposes a layer of mineral-depleted collagen fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Most of the current adhesive systems use an acidic conditioner to prepare the dentin surface for the bonding components. 8 When dentin is etched with phosphoric acid concentrations, the smear layer is completely removed and the dentin surface is morphologically changed due to the dissolution of hydroxyapatite crystals. This process widens the dentinal tubules and exposes a layer of mineral-depleted collagen fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Pulpal temperature increases in relation to the curing of tooth coloured restorations is well documented and is a result of the exothermic setting reaction of the composite and the energy absorbed from the light used to initiate cure. 4,[6][7][8][9][10] Overall, these studies have reported a pulpal temperature increase of 10-14°C but most of the work in this area has been confined to conventional light curing units. Duret 11 found, however, that a plasma arc lamp (Apollo 95E) produced an intra-pulpal temperature rise of 2.2°C with a four second exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, dual-cured resin cements are the best choice for luting ceramic dentures to obtain an esthetically pleasing result, as well as to minimize the disadvantage of polymerization shrinkage of composites 24) . With light-cured resin cements there is a temperature increase caused by the exothermal reaction of the material and heat from the curing unit light 22) , and when some of the light cured cements are polymerized with certain LCUs, temperature increases exceeding 12°C can be produced 22) . Photo-activation is performed with visible light belonging to the blue area of the electromagnetic spectrum to excite camphorquinone (the most commonly used photo initiator in resin cement), which has an absorption spectrum in the interval between 400 and 500 nm 9) .…”
Section: Introductionmentioning
confidence: 99%